Safranine-O Incorporated in F127 Nanocarriers Reduces the Contamination of Staphylococcus aureus in Sheep’s Milk - B. M. Rodrigues; R. C. Silva Junior; B. B. Saraiva; H. L. Perez; L. F. Maia; W. Caetano; C. V. Nakamura; B. A. Abreu Filho; M. S. S. Pozza (Tropical Animal Science Journal, 2022)
Mastitis caused by Staphylococcus aureus uses antibiotics as conventional treatment, a practice that has led to bacterial resistance. Therefore, the photodynamic inactivation of microorganisms (PDIM), has the advantage of inactivating pathogens without leading to the selection of resistant microorganisms. The objective of the study was to evaluate the antimicrobial activity of the photosensitizer (PS) Safranine-O (Sf), incorporated in the nanocarrier Pluronic® F127 against strains of S. aureus isolated from sheep milk. The reduction of contamination in experimentally contaminated milk and Muller Hilton Broth (MHB), the formation of microbial biofilm, and its effect as post dipping in the decrease of total mesophilic aerobic and Staphylococcal counts in milk were evaluated. Three strains of S. aureus (SO1, SO3, SO4) and a coagulase-negative Staphylococcus (CNS) strain (SO2) were identified through the nuc and coa genes and all were sensitive to PDIM. The minimum inhibitory concentration (MIC) ranged from 1.18 to 18.75 mg/mL in the different isolates. The SO4 strain was resistant to Ampicillin and Trimetropim. When the microorganisms were cultivated in milk and MHB, there was a reduction in staph counts by 97.33% and 99.63%, respectively. In stainless steel coupons, photoinactivation reduced S. aureus adhesion by up to 45.92% (milk) and 99.5% (MHB) (p<0.05). The photoactivated Sf was similar to commercial lactic acid when applied as a dipping powder. These results showed that Sf mediated PDIM effectively inactivated pathogens that cause mastitis and reduced milk contamination.